In the Gulf, Trinidad - Strong (Davidson and Todd, [Trinidad and Tobago], 2011)
Postcard features four men on a boat in the Gulf of Paria, off the island of Trinidad, West Indies.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Fishing--Trinidad and Tobago; Fishers--Trinidad and Tobago